Mercapto-functionalized polyhedral oligomeric silsesquioxane as a soluble support for the synthesis of peptide thioesters. (23rd November 2021) - Perry, Kimberly; Sui, Binglin; Li, Yangmei
Graphical abstract: Abstract: The revival of peptide-based drugs has led to the increasing demand for the development of large-scale synthesis of these complex molecules. To meet this demand, the use of mercapto-functionalized polyhedral oligomeric silsesquioxane (POSS-SH) as a soluble support for the synthesis of a model pentapeptide POSS-thioester is reported. The synthetic process provided a total yield of 62% for the pentapeptide POSS-thioester and the 1 H NMR spectra validated the high purity of the products. The successful synthesis of the pentapeptide POSS-thioester with high yield and purity provides a promising way to the scale-up chemical synthesis of peptide thioesters, peptides, peptide amides, cyclic peptides, and even proteins.